PENGGUNAAN MEDIA PEMBELAJARAN BASIC TRAINER ELECRONICS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN DASAR-DASAR KEJURUAN KELAS XMK TDK SMK NEGERI 1 BATAM - Nelma Busra; Jaenuddin Jaenuddin (Jurnal Liga Ilmu Serantau, 2025)
The changes in the curriculum at Center of Excellence schools have resulted in several adjustments to productive subject learning, particularly in lesson hours and subject distribution. With the merging of several subjects into a single subject, namely Basic Vocational Studies, the available time has been further reduced, which in turn causes students to require a relatively longer time to understand the material. Furthermore, with Physics being merged into the IPAS subject—which focuses more on natural, social, and economic sciences—students’ needs related to vocational or engineering fundamentals have yet to be fully met. Learning media is a tool used in the teaching and learning process that stimulates students’ interest, thinking, and attention so that learning objectives can be achieved. The use of learning media also serves to enhance the effectiveness of the learning process, making it more efficient despite the limited time available. This study aims to determine the extent to which students’ learning outcomes improve after the implementation of the Basic Trainer Electronics learning media in Basic Vocational Studies. This classroom action research was conducted in two cycles. In Cycle I, out of 20 students, only 3 students reached the Minimum Mastery Criteria (KKM), or only 15% achieved mastery, with an average score of 55.6. In Cycle II, the number of students achieving mastery increased to 20 out of 20 students, or 100%, with the average score increasing to 78.3. The results show a comparison between Cycle I and Cycle II: in Cycle I, the average score was 55.6 with a mastery percentage of 15%, while in Cycle II, the average score increased to 78.3 and the mastery percentage rose to 100%. Based on the KKM score of 75, the improvement in Cycle II was 85%. From the results of this study, it can be concluded that the use of Basic Trainer Electronics learning media can improve the learning outcomes of XMK TDK students in the Basic Vocational Studies subject. The use of Basic Trainer Electronics learning media can be considered for future research, especially in productive subjects.